English for journalists - Hicks, Wynford, 1942- (London : Routledge, 2013)
English for Journalists has established itself as an invaluable guide to the basics of English in newsrooms the world over, focusing on the essential aspects of writing, from reporting speech to the house styles and jargon central to the language of journalism. Written in a highly accessible and engaging style, English for Journalists covers the fundamentals of grammar, spelling, punctuation and journalistic writing, with all points illustrated through a series of concise and illuminating examples. The book features practical, easy to follow rules, the correct and incorrect ways to report stories, and examples of common mistakes and problem words in journalistic writing. The twentieth anniversary edition adds a new introduction to the work from author Wynford Hicks, as well as updated examples throughout to improve accessibility, and a revised first chapter on the state of English today. This is an essential guide to written English for all practicing journalists and students of journalism today.
Includes bibliographical references (pages 189-190) and index.
Keywords: English language -- Grammar -- Handbooks, manuals, etc; Journalism -- Style manuals